2014
DOI: 10.1146/annurev-astro-082812-141003
|View full text |Cite
|
Sign up to set email alerts
|

Hot Accretion Flows Around Black Holes

Abstract: Black hole accretion flows can be divided into two broad classes: cold and hot. Cold accretion flows, which consist of cool optically thick gas, are found at relatively high mass accretion rates. Prominent examples are the standard thin disk, which occurs at a fraction of the Eddington mass accretion rate, and the slim disk at super-Eddington rates. These accretion flows are responsible for luminous systems such as active galactic nuclei radiating at or close to the Eddington luminosity and black hole X-ray bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

48
1,275
1
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,359 publications
(1,336 citation statements)
references
References 582 publications
(1,041 reference statements)
48
1,275
1
12
Order By: Relevance
“…The accretion mode transition is mainly triggered by the dimensionless mass accretion rate ṁ (m M M criṫ˙= ), which depends sensitively on the viscosity parameter α (see Narayan et al 1998;Yuan & Narayan 2014, for reviews). The critical mass accretion rate m criṫ can be estimated by equating the ionelectron equilibration timescale to the accretion timescale of an advection-dominated accretion flow (ADAF; Narayan et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The accretion mode transition is mainly triggered by the dimensionless mass accretion rate ṁ (m M M criṫ˙= ), which depends sensitively on the viscosity parameter α (see Narayan et al 1998;Yuan & Narayan 2014, for reviews). The critical mass accretion rate m criṫ can be estimated by equating the ionelectron equilibration timescale to the accretion timescale of an advection-dominated accretion flow (ADAF; Narayan et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The outflow can transport energy, momentum, mass, heavy elements from the accretion disc and/or the vicinity of central region to the host galaxy and IGM, which regulate the efficiency of accretion onto the central supermassive black hole (e.g., Emmering et al 1992;Konigl & Kartje 1994), and influence the evolution of the host galaxy and surrounding environment (e.g., Tremonti et al 2007;Cattaneo et al 2009;Yuan & Narayan 2014;Ishibashi & Fabian 2014). Intrinsic absorption lines, including BALs, mini-BALs and NALs, are often utilized to study properties of the quasar outflow.…”
Section: Introductionmentioning
confidence: 99%
“…During the low/hard state, defined as an accretion state in X-ray binaries dominated by a flat powerlaw emission and a strong band limited noise in the Fourier power spectra (Remillard & McClintock 2006), the inner part of the truncated disc is usually filled with a hot, relativistic electron plasma (Yuan & Narayan 2014) along with intense magnetic fields (Esin et al 1997). The idea that such magnetized hot flow could be the birthplace of optical photons by means of electron-cyclotron emission, was introduced by Fabian et al (1982) and successfully explained some of the fast variability observed from GX 339-4 (Motch et al 1983), 20-sec X-ray QPOs and the observed X-ray/optical anticorrelation in the CCF.…”
Section: Introductionmentioning
confidence: 99%